Determinants of credit risk in Hong Kong banks - Hung, Ka Ho (2019)
The purpose of this dissertation is to study the bank-specific and macroeconomic determinants of credit risk in Hong Kong. The fixed effects model approach is used so as to study credit risk determinants in 22 commercial banks from 2012 to 2017. Moreover, 5 bank-specific and 3 macroeconomic variables are used to assess their influence on credit risk. While there are plenty of studies conducted regarding credit risk determinants in different countries, limited studies have examined credit risk determinants in East-Asian countries, especially in Hong Kong. Hence this dissertation aims to investigate whether the past findings of relevant studies are applicable in Hong Kong banks.